2017
DOI: 10.1530/joe-16-0371
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the development of prolactinoma in mice overexpressing hCGβ: role of TGFβ1

Abstract: Female transgenic mice that overexpress the human chorionic gonadotrophin β subunit (hCGβ+) develop prolactinomas, whereas hCGβ+ males do not. The high levels of circulating hCG induce massive luteinization in the ovary of hCGβ+ females, and progesterone becomes the primary steroid hormone produced, but estradiol remains at physiological level. The involvement of high levels of progesterone in lactotroph proliferation is not clearly understood; hence, the pathogenesis of prolactinomas in hCGβ+ females remains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 45 publications
2
27
0
Order By: Relevance
“…Other studies have presented evidence that differential expression of estrogen receptor α and transforming growth factor β 1 may play a role in the difference seen in tumor pathogenesis between the genders, though the results of these studies are yet to be confirmed. 13,26 Previous studies have also shown differences in disease history between men and women with prolactinomas. Specifically, men have been previously shown to have shorter duration of symptoms prior to surgery, higher levels of preoperative serum prolactin levels, and more medically refractory disease.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have presented evidence that differential expression of estrogen receptor α and transforming growth factor β 1 may play a role in the difference seen in tumor pathogenesis between the genders, though the results of these studies are yet to be confirmed. 13,26 Previous studies have also shown differences in disease history between men and women with prolactinomas. Specifically, men have been previously shown to have shorter duration of symptoms prior to surgery, higher levels of preoperative serum prolactin levels, and more medically refractory disease.…”
Section: Discussionmentioning
confidence: 99%
“…All primers showed similar efficiencies of ~95–100%. A housekeeping gene, Cyclophilin B ( Cyp B ), was used as an internal control to normalise differences in the amount of starting template between samples, as described previously . Target gene expression was quantified using the comparative CT method (ΔCT).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, FS cells produce numerous cytokines and growth factors, including interleukin-6 (IL-6), follistatin, basic fibroblast growth factor, transforming growth factor β (TGF β), VEGF and leukemia inhibitory factor, which all regulate lactotropic cell proliferation and prolactinoma development [47]. The TGFβ1 expression was reduced in human and animal prolactinomas [91,92]. Estradiol inhibits most of the components of the TGFβ1 system, and this mechanism seems to be of importance with regard to the balance and negative control of the function of lactotropic cells [40] (Figure 1).…”
Section: Effects Of Estradiol On the Cellular Microenvironment In Thementioning
confidence: 99%